Advances in Peritoneal Dialysis in Acute Kidney Injury - Ponce, Daniela [UNESP]; Balbi, André Luis [UNESP]; Amerling, Richard (Karger, 2012)
Peritoneal dialysis (PD) is a simple, safe, cheap, and efficient renal replacement therapy method. It can correct metabolic disorders and fluid overload in acute kidney injury (AKI) patients both in and out of the intensive care unit. Use of PD in AKI is enhanced by placement of a Tenckhoff catheter, which can be safely accomplished at the bedside. Some PD modalities, such as high-volume PD and continuous-flow PD, can provide dialysis doses and efficiency comparable to extracorporeal blood purification methods. PD is particularly suitable for neonates, children, and patients with refractory heart failure or who are otherwise hemodynamically unstable. PD should be considered in situations where systemic anticoagulation and/or vascular access are problematic. PD is limited by a lower efficiency that may produce inadequate renal replacement in larger and/or severely hypercatabolic patients. Fluid removal can be unpredictable, there is a risk of infection, and possible issues with mechanical ventilation. In this article, we discuss the use of PD in AKI, with emphasis on recent advances. Copyright (c) 2012 S. Karger AG, Basel
Keywords: Peritoneal dialysis; Acute kidney injury; Renal replacement therapy